Measurement of the ¯B0s→D−sD+s and ¯B0s→D−D+s effective lifetimes - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physical review letters, 2014)
The first measurement of the effective lifetime of the ¯B0s meson in the decay ¯B0s→D−sD+s is reported using a proton-proton collision data set, corresponding to an integrated luminosity of 3 fb−1, collected by the LHCb experiment. The measured value of the ¯B0s→D−sD+s effective lifetime is 1.379±0.026±0.017 ps, where the uncertainties are statistical and systematic, respectively. This lifetime translates into a measurement of the decay width of the light ¯B0s mass eigenstate of ΓL=0.725±0.014±0.009 ps−1. The ¯B0s lifetime is also measured using the flavor-specific ¯B0s→D−D+s decay to be 1.52±0.15±0.01 ps.
Im Titel erscheint das Zeichen ¯ als Querbalken über dem B. Das s ist stets tiefgestellt und die 0 sowie die Zeichen - und + erscheinen hochgestellt
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, A. Affolder, Z. Ajaltouni, J. Albrecht, F. Alessio, M. Alexander, S. Ali, G. Alkhazov [und 665 weitere]
Gesehen am 15.09.2020